Going Open in University & Libraries challenges and applications - Gouveia, Luis Borges (2017)
The digital and the almost ubiquitous existence of computers, mobile devices and computer networks turns data and informa;on easily accessible and thus create new challenges. It impacts not just the way we preserve informa;on but also how we store and organize it, forcing new forms to curate, discover and tackle with the economy of authorship, intellectual property, and editorship rights which are being eroding tradi;onal barriers to ac;vi;es like reading, usage, exploring and transforming both data and informa;on into value. As a result, the needs to be fulfill and services provided by libraries urge to consider a more digital context allowing a move to adapt and evolve (being smart) in order to provide digital informa;on along with more tradi;onal services in a sustainable way. This presenta;on discusses some of the challenges and applica;ons that the open movement may provide for the years to come. Can we consider that academic libraries candidates to be part of the digital transformation?